1995
DOI: 10.1002/1520-6807(199507)32:3<190::aid-pits2310320306>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

School-linked and school-based health services: A renewed call for collaboration between school psychologists and medical professionals

Abstract: Health care and education reform provide opportunities to build systems that promote rather than retard collaboration between school psychologists and medical professionals. School-linked and school-based health services (SLSBHS) are a family of approaches that provide medical, social, and mental health services to students through school settings. These services have potential to provide more than acute care or first-aid services. SLSBHS provide medical care to uninsured children, students with chronic medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Evidence exists that the case management team approach, under the direction of support service professionals, reduces fragmentation and redundancy of services, increases treatment acceptability, increases generalization of treatment gains, and increases the school's success in managing behavior and learning environments (Conoley & Conoley, 1991). Service delivery also becomes more outcome oriented, consumer driven, and cost conscious (Romualdi & Sandoval, 1995;Shaw et al, 1995), as well as less intimidating and easier to access (Dowling & Taylor, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence exists that the case management team approach, under the direction of support service professionals, reduces fragmentation and redundancy of services, increases treatment acceptability, increases generalization of treatment gains, and increases the school's success in managing behavior and learning environments (Conoley & Conoley, 1991). Service delivery also becomes more outcome oriented, consumer driven, and cost conscious (Romualdi & Sandoval, 1995;Shaw et al, 1995), as well as less intimidating and easier to access (Dowling & Taylor, 1989).…”
mentioning
confidence: 99%
“…These schools are now successfully applying this model in order to expand their school-based clinics Shaw et al, 1995;Dryfoos, 1993). found that a truly comprehensive services program must include sequential services in eight different areas: health education, physical education, health services, nutrition services, health promotion, counseling/psychological/social services, a healthy school environment, and parent/community involvement.…”
mentioning
confidence: 99%
“…Despite the theoretical understanding of IPE and its collaborative practice in health care for more than a decade in Western countries, aspects of interprofessional practice are few and far between in the provision of school health services (Shaw et al . , Aldinger et al . , Sulkowski et al .…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries such as the US and Australia, school nurses are often the providers of school health services (Brener et al 2007). Despite the theoretical understanding of IPE and its collaborative practice in health care for more than a decade in Western countries, aspects of interprofessional practice are few and far between in the provision of school health services (Shaw et al 1995, Aldinger et al 2008, Sulkowski et al 2011. Contrary to WHO's recommendation, the health service delivery mode by school nurses involves little collaboration with other health professionals; rather, they deliver care in silos (Sulkowski et al 2011). In Hong Kong, the concept of school nurse was introduced only a few years ago, in 2009, and few mainstream local schools have a school nurse stationed on site (Lee 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, implementation of multiprofessional school-based health care services has shown to (a) have positive effects on students' academic achievement (Brown & Bolen, 2008;Shaw, Kelly, Joost, & Parker-Fisher, 1995), (b) reduce absence from school (Gall, Pagano, Desmond, Perrin, & Murphy, 2000), and (c) reduce aggressive as well as substance use behaviors among students (see Brown & Bolen, 2008). Nevertheless, research on multiprofessional teams and collaboration in school settings has shown a lot of pitfalls or problems:…”
mentioning
confidence: 99%